Predicting academic performance - Marcos Gallacher (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2005)
This paper discussed advantages and disadvantages associated with the use of admission tests as predictors of performance in undergraduate studies programs. The paper analyzes performance of economics and business administration students. This performance is linked to admission tests results. The paper also analyzes aspects of performance related to (i) differential progress through time, and (ii) differences in the extent to which students have areas of interest/ability. The paper concludes that admission tests are a usefull tool even when predictions derived from them are far from perfect.
Keywords: I2; J24; 330